2021
DOI: 10.1590/1806-9282.20200778
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of patients with essential thrombocythemia in terms of risk of thrombosis

Abstract: OBJECTIVE:The aim of this study was to compare the incidence of factors associated with an increased risk of thrombosis in patients with essential thrombocythemia.METHODS: A total of 200 patients followed-up in our unit with a diagnosis of essential thrombocythemia in 13 years were analyzed retrospectively.RESULTS: Of the study participants, 60.5% were females and 39.5% were males, with an overall mean (±SD) age of 54.93 (±14.21) years. In 119 patients, Janus Kinase 2 was positive with 56.3% of cases. When two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
(30 reference statements)
2
2
0
Order By: Relevance
“…Furthermore, it has been highlighted that MPN is associated with a high risk of thrombotic and thromboembolic events when compared with the general population, and is also associated with increased hematopoietic counts (40), which was also observed in the present study. This fact may be explained by the presence of a high VAF of JAK2V617F (≥50%), which likely stimulates deregulation signaling in hematopoietic progenitor cells and may be potentialized by the presence of other variants in genes such as CALR and MPL; these are directly implicated in platelet activation and increased platelet account (40).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Furthermore, it has been highlighted that MPN is associated with a high risk of thrombotic and thromboembolic events when compared with the general population, and is also associated with increased hematopoietic counts (40), which was also observed in the present study. This fact may be explained by the presence of a high VAF of JAK2V617F (≥50%), which likely stimulates deregulation signaling in hematopoietic progenitor cells and may be potentialized by the presence of other variants in genes such as CALR and MPL; these are directly implicated in platelet activation and increased platelet account (40).…”
Section: Discussionsupporting
confidence: 87%
“…The effects of JAK2 VAF are well established; however, the specific populations affected are poorly understood. Through the comparison of JAK2V617F VAF, it was shown that patients from the state of Amazonas with PV had a JAK2V617F VAF that was higher than those diagnosed with ET, and individuals with a VAF of ≥50% had more thrombo-hemorrhagic events and a slight prolongation in coagulation tests, especially in PT-INR and aPTT when compared with those with a VAF of <50%, which is that not dissimilar to previous studies (40,46). This fact directly suggests that individuals with a high JAK2V617F VAF exhibit increased intracellular signaling, cellular activation, and possible alterations in coagulation factors, thus contributing to the deregulation of hemostasis.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…More than half of ET patients are JAK2V617F mutation-positive. According to our present knowledge, JAK2 mutation has been an independent factor for thromboembolic events; however, the precise mechanism remains unknown (3). Most ET patients enjoy a near-normal life expectancy (4).…”
Section: Introductionmentioning
confidence: 94%